Price Fluctuations And Catch Yields Of Scombridae Fish In Singkawang City During 2019-2023 - Risqi Pricillia Nanda; Indra Mahyudi S (PAKIS JOURNAL INSTITUTE, 2025)
. The Scombridae fish group belongs to the type of pelagic fish most frequently caught in Indo-Pacific waters, including the Indonesian archipelago, and has a relatively high economic value. In Singkawang City, the catch of Scombridae species such as tuna, mackerel, and Indian mackerel shows considerable fluctuations both in terms of price and catch volume. Therefore, the purpose of this study is to analyze the fluctuations in catch and price of Scombridae fish, namely Spanish mackerel , narrow-barred mackerel, frigate tuna, bullet tuna, and Indian mackerel. The data used in this study are secondary data obtained from https://portaldata.kkp.go.id/portals/data-statistik/layer1. From this website, the data collected include fish catch and price data from 2019 to 2023. The results show that for the catch data, spanish mackerel, bullet tuna, and indian mackerel were recorded during the 2019–2023 period, with the highest catches respectively being 606,650 kg for spanish mackerel, 203,730 kg for frigate tuna, 776,030 kg for bullet tuna, and 275,760 kg for indian mackerel. Frigate tuna had no recorded catch in 2020, with its highest catch recorded in 2021 at 203,730 kg and the lowest at 105,780 kg. Meanwhile, for the spanish mackerel, catches were only recorded in 2021 with a total of 17,000 kg. As for fish prices, the highest was spanish mackerel, reaching Rp 60,000 per kg in 2021, and even its lowest price remained higher than other Scombridae species, at Rp 45,000 per kg. Meanwhile, the lowest price among the five Scombridae species observed was Indian mackerel, at Rp 15,000 per kg.